ANALISIS KRITIS KONSELING KIPAS BERBASIS BUDAYA NUSANTARA SEBAGAI MODEL KONSELING DALAM DUNIA PENDIDIKAN - Ramanta, Deka (FKIP Universitas Wisnuwardhana, 2019)
Guidance and counseling is a unity of the world of education whose existence is increasingly tested from time to time and increasingly needed. However, so far the implementation of guidance and counseling still adopts an approach based on western culture. Intensive Adaptive Progressive Structural Counseling (KIPAS) created by Andi Mappriare-AT is present as a type of guidance and counseling based on Nusantara culture. The focus on writing this article includes a description of a critical analysis of the KIPAS model. The cultural background promoted by the KIPAS model is the main advantage of this counseling approach, making it very effective in the application of guidance and counseling services in Indonesia. In addition, there are some criticisms of the KIPAS model, especially related to the KIPAS model counseling steps. As a counseling mapping model based on the Nusantara culture, the KIPAS model needs to be given appreciation and further development efforts from all practitioners and academics in the field of guidance and counseling. Keywords: critical analysis, guidance and counseling, KIPAS